Awareness of sailors on first aid and the use of AED - Czarnecki, Mariusz (Journal of Education, Health and Sport, 2017)
Determination of consciousness of an injured person and giving first aid are crucial in the proper conduct of the survival chain. The aim of the study was to show the sailors’ awareness about first aid and the use of automated external defibrillator (AED). Study group consisted of 261 people of all ages, including 146 men and 76 women. 138 people from study group declared to have achieved higher education, 77 – average education and 7 – basic education. 195 people practice sailing for leisure and 27 surveyed people are professional sailors. All surveyed subjects sail in various periods of the year. For the sake of the study, a fully anonymous questionnaire was developed. Study showed, that sailors’ awareness of first aid and the use of AED is not sufficient and first aid courses should address important legal aspects of first aid, including issues related to the use of automated external defibrillator.